PKHD1 protein encoded by the gene for autosomal recessive polycystic kidney disease associates with basal bodies and primary cilia in renal epithelial cells - Zhang, Ming-Zhi (National Academy of Sciences, 2004)
Mutations of the polycystic kidney and hepatic disease 1 (PKHD1) gene have been shown to cause autosomal recessive polycystic kidney disease (ARPKD), but the cellular functions of the gene product (PKHD1) remain uncharacterized. To illuminate its properties, the spatial and temporal expression patterns of PKHD1 were determined in mouse, rat, and human tissues by using polyclonal Abs and mAbs recognizing various specific regions of the gene product. During embryogenesis, PKHD1 is widely expressed in epithelial derivatives, including neural tubules, gut, pulmonary bronchi, and hepatic cells. In the kidneys of the pck rats, the rat model of which is genetically homologous to human ARPKD, the level of PKHD1 was significantly reduced but not completely absent. In cultured renal cells, the PKHD1 gene product colocalized with polycystin-2, the gene product of autosomal dominant polycystic disease type 2, at the basal bodies of primary cilia. Immunoreactive PKHD1 localized predominantly at the apical domain of polarized epithelial cells, suggesting it may be involved in the tubulogenesis and/or maintenance of duct–lumen architecture. Reduced PKHD1 levels in pck rat kidneys and its colocalization with polycystins may underlie the pathogenic basis for cystogenesis in polycystic kidney diseases.